"Non-violent evangelism": a look at how members of evangelical faith-based organizations share faith with service recipients in Southern, Ontario, Canada. Issue 3 (3rd July 2021) - Gokani, Ravi; Caragata, Lea
ABSTRACT: This present work shares data from a mixed-methods study in Southern Ontario, Canada, focused on understanding faith sharing (often called evangelism or proselytism) within evangelical faith-based organizations. The study figures against the backdrop of the relatively scant literature on understanding evangelism in social service settings. The findings reveal multiple ways in which faith-based organizations seek to evangelize clients "non-violently", i.e., in a fashion that is not forceful or coercive. Here we focus on three: (1) through sharing and imparting a worldview; (2) through faith as a service modality; and (3) through social support. Analyzed against the backdrop of existing literature on faith-based organizations and ethical social service delivery, our findings suggest the need for further inquiry into social service delivery by faith-based organizations (FBOs). The paper discusses some valuable elements of the service provided by FBOs but also raises critical questions about client self determination and autonomy and service free from coercion – even if faith-sharing is in its gentlest and most well-intentioned form.